Hygienic assessment of the factual nutrition of able-bodied population in the observation area of the Zaporizhzhia nuclear power plant (Environment & Health, 2017)
Background: Assessment of the safety of nuclear energy for the environment and the human health is one of the priorities of science and project-oriented activity. Last years it is especially important due to the structural changes in the state administration, prolonged social-and- economic crisis in the country, decrease of living standards and significant deterioration in medical service and nutrition. The results of experimental studies and medical- and-epidemiological observations indicate that the digestive system is sensitive to ionizing radiation. The observation area (OA) of the Zaporizhzhia Nuclear Power Plant covers a part of the Zaporizhzhia and the Dnipropetrovsk regions. However, studies of its impact on the environment and the health of the population have not been performed in recent years. Assessment of the nutrition status of the population, living in the observation area of this nuclear power plant, is especially topical now.Objective: We estimated a state of the factual population nutrition of the observation areas of the nuclear power facilities of Ukraine on the example of the Zaporizhzhia NPP from the hygienic point of view.Materials and methods: We used bibliographic, sociological, analytical, and statistical methods.Results: Emission of the basic dose forming radionuclides 137Cs and 90Sr into the environment took place in the process of the operation the Zaporizhzhia NPP but their content did not exceed a “zero background”; contamination levels were unequal and had a territorial difference. The factual nutrition of the residents of the Zaporizhzhia NPP observation area does not meet the requirements of a balanced diet by the content of the basic nutrients in a daily intake.Conclusions: Obtained data indicate the possibility of safe living of the population in the observation area of the Zaporizhzhia NPP according to the radiation factor. Instability in the levels of food contamination by plant’s emissions indicates the need of constant monitoring of their composition and impact on the health of the residents of the observation area.
Keywords: nuclear power plants; radiation protection; observation area; nutrition of population